6502 SAYILI TKHK ÇERÇEVESİNDE TÜKETİCİ İŞLEMİ NİTELİĞİ TAŞIYAN ESER TESLİM SÖZLEŞMESİNDE AYIPTAN DOĞAN SORUMLULUK İÇİN UYGULANACAK HÜKÜMLER - (:unkn) unknown (My University, 2016)
Eser teslim sözleşmeleri, gerek 818 S. BK, gerekse 6098 S. TBK hükümlerinde eser sözleşmesinin bir türü olarak kabul edilmektedir. Bu nedenle TBK m. 471/IV hükmünde, ayıptan sorumluluk için satıcının sorumluluğu hükümlerine yapılan yollama, iki farklı sorumluluk tipinin bir arada uygulanması nedeniyle ortaya çıkacak sorunlar öne sürülerek eleştirilmekteydi. Çalışmamızda 6502 S. TKHK'nun ve ilgili düzenlemelerde dikkate alınan 1999/44/AT Direktif'inin hükümlerini de dikkate alarak, tüketici işlem niteliğindeki eser teslim sözleşmelerine uygulanacak hükümleri belirlemeye çalışacağız.

Work delivery contracts are considered a type of independent work contract according to both Code of Obligations, No: 818 and Turkish Code of Obligations, No: 6098. Therefore, the reference to norms with regards to obligations of the seller in the case of obligations due to defects in the Turkish Code of Obligations, no 471/IV has been criticized due to the potential problems, which arise due to the application of two different types of obligations jointly. In this article, we will try to identify the norms which are applicable to consumer transaction type of work delivery contracts, taking into consideration the 1999/44/EU Directives which have also been provisioned in the Consumer Protection Law, No: 6502 and relevant regulations.
(The Norms That are Applicable To Obligations Due To Defect In Work Delivery Contracts That Qualify as Consumer Transaction Within The Framework of Consumer Protection Act, No: 6502)
Keywords: Hukuk